Nonalcoholic fatty liver disease is associated with excessive calorie intake rather than a distinctive dietary pattern - Wehmeyer, Malte H. (Medicine (Baltimore), 2016)
We aimed to assess the dietary patterns associated with nonalcoholic fatty liver disease (NAFLD) and the efficacy of dietary interventions in a real-life setting at a tertiary medical center in Northern Germany. Clinical and laboratory data as well as data obtained by a semiquantitative food frequency questionnaire of 55 consecutive patients diagnosed with NAFLD were compared to an age and gender-matched cohort of 88 healthy individuals by univariate analysis. The efficacy of the dietary intervention was assessed in a subgroup of 24 NAFLD patients 6 months after receiving dietary advice. Macronutritional components of the diet were normalized for absolute daily energy intake. NAFLD patients consumed more calories per day as compared with healthy controls (P <0.001). The absolute amounts of most nutritional components ingested by NAFLD patients were higher than those of the controls. However, there were no significant differences with regards to the relative consumption of carbohydrates (P = 0.359), fat (P = 0.416), and fructose (P = 0.353) per 1000 kcal energy intake. NAFLD patients displayed a higher intake of glucose/1000 kcal (P = 0.041) and protein/1000 kcal (P = 0.009) but a lower intake of fibers/1000 kcal (P < 0.001) and mineral nutrients/1000 kcal (P = 0.001) than healthy controls. In the longitudinal analysis patients significantly reduced their caloric intake and their ALT levels improved 6 months after the dietary counselling (P < 0.001). Our data from a German real-life cohort demonstrate that dietary patterns of patients with NAFLD display great variability and little disease specificity, while the most distinctive feature compared with healthy controls was higher energy intake in NAFLD patients.